Modeling of control devices for sensor wireless ZigBee networks - Барило, Григорій Іванович; Гельжинський, Ігор Ігорович; Грицик, Ростислав Іванович; Іванюк, Христина Богданівна; Кус, Наталія Іванівна (Eastern-European Journal of Enterprise Technologies, 2012)
The article concerns the peculiarities of the design of the control devices of the wireless sensor networks based on the IEEE 802.15.4 standard, which are widely used in the control systems of technological processes and monitoring of various objects. The networks of such systems are based on the standardized radio modules of ZigBee technology with the integrated microprocessor software. To optimize the design process of such devices it is reasonable to use the appropriate software debugging tools. A method of the debugging of the control devices built on microcontrollers SS25hh (Texas Instrument) using Proteus software environment was suggested. In this environment, a working model of the device was designed. The device can operate in a mode of a router or a final device and transfer the information from primary sensors. A modeling of the measurement process of the analog and digital input signals, coming from sensory transducers, was carried out. An algorithm for setting the controller for the operation of the environmental monitoring system was presented. The debugging procedure of the internal software of the microcontroller was shown to provide the basic modes of the processes of transfer and information exchange. A possibility of designing of the printed circuit boards with a built-in antenna for the radio path as part of the environmental monitoring system was presented